Investigation of stress resulting from laboratory experiments in fish - Hegyi, Árpád; Béres, Tibor; Kovács, Róbert; Kotrik, László; Urbányi, Béla (Animal welfare, Ethology and Housing Systems (AWETH), 2008)
In the process of laboratory experiments (either in tanks or aquaria) fish are continuously exposed to several external effects (e.g. seining, induced spawning, stocking, treatment against diseases, blood sampling, temperature, etc.). Induced environmental stress has a significant influence on the homeostasis of fish as on that of any vertebrates. Environmental stress affects metabolism (e.g. that of carbohydrates, lipids, N- containing materials, vitamins and minerals), and this can influence the effectiveness of experiments. An improperly chosen experimental work phase (such as too high stocking density) can increase the concentration of some blood plasma parameters several times and can even lead to death of animals.Stress effects influence vital processes in different ways and directions: general health state can deteriorate, growth rate can decrease, gills can be damaged, stomach and intestinal function can be disrupted, brain structure can be altered, the central nervous system can be damaged, behavior can be changed and the hypothalamus-pituitary-gonad axis can be blocked.The effect of aquaria, weekly seining and blood sampling on blood plasma glucose and serum/plasma fructosamine concentrations was investigated in long-term, four-week experiments. Results have shown that no significant differences were detected in the levels of blood plasma components suitable for the measurement of mid- and long-term stress during consecutive blood samplings. Thus, the adverse effects of work phases on experimental results do not have to be taken into account in well-designed and executed investigations.
Keywords: fish; stress; blood plasma glucose; serum/plasma fructosamine